PENGEMBANGAN WORKSHEET TEMATIK-INTEGRATIF PADA MATA PELAJARAN IPA TERPADU UNTUK MENUMBUHKAN KETERAMPILAN BERPIKIR KERITIS SISWA - Hunaepi Hunaepi; Muhali Muhali; Saiful Prayogi (Lensa: Jurnal Kependidikan Fisika, 2013)
The research was conducted to improve the Critical Thinking Capability in detail: 1) Describe the thematic-integrative worksheet on integrated IPA Subjects, 2) Measure the critical thinking skills of students as the effect of the thematic-integrative Worksheet material, and 3) Describe the student's response to the teaching material Worksheet thematic-integrative. The resulting product development is an thematic-integrative Worksheet to support a learning process that can improve critical thinking skills. The thematic-integrative worksheets developed have met the criteria of validity and according to the expert. The test results have shown that the thematic-integrative Worksheet teaching materials are more effective. All learning tools used are in valid categories and are eligible for use. The results of the first trial showed that students' critical thinking skills were averaged 76.7 (critical categories), while the second test reached an average of 84.4 (very critical). Based on the analysis result, it is found that the thematic-integrative worksheet developed can develop critical thinking skill.